(3JQJjH GdCQHYjf MOjKG dGHf LeGYIs - (3GdSjhWj GdNVjQj, CHh GdaVd, LdGd GdOjf, YHO GdQMef Hf CHj HcQ Hf eMeO, J (B911 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HYO GdHSedI ; jbhd YHO GdQMef Gddg CMeO gPG JQJjH CQHYjf MOjKG CdagG GdTjN YR GdOjf Hf LeGYI s
(3BNQgG (B:s
(3Y Gdjejf GdaGLQI JOY GdQjGQ HdGbYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 301s
(3eYLe GdeDdajf (B2 / 82s
(3TPQGJ GdPgH (B8 / 51s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdMOjK hGdeUWdMs